Prevalence of sleep apnoea and snoring in hypertensive men: a population based study. Issue 7 (1st July 2002) - Sjöström, C; Lindberg, E; Elmasry, A; Hägg, A; Svärdsudd, K; Janson, C
Abstract : Background: Several studies have reported an association between sleep disordered breathing (SDB) and hypertension (HT) but there is still a debate as to whether this is an effect of confounders. Some researchers have found an age dependent relationship between SDB and HT with higher risk at lower ages. A case-control study was performed in hypertensive men and non-hypertensive male controls matched for age and body mass index to assess whether there is an independent association between SDB and HT. If so, we further wanted to investigate whether this effect is age dependent. Methods: An overnight sleep study was performed in a population based, age stratified sample of 102 hypertensive men aged 43–82 years and 102 non-hypertensive controls. Results: Hypertensive subjects had a significantly higher prevalence of SDB than non-hypertensive subjects (apnoea-hypopnoea index (AHI): 10.8 v 7.3; desaturation index (DI): 8.5 v 5.2; AHI ≥10: 37% v 24%, p<0.05; DI ≥10: 29% v 12%; lowest desaturation: mean (SD) 81.9 (7.3) v 84.7 (6.1), p<0.01). After adjusting for neck circumference and physical inactivity, DI ≥10 and lowest desaturation were still independent predictors of HT with adjusted odds ratios of 2.3 (95% CI 1.0 to 5.3) and 0.94 (95% CI 0.89 to 0.99), respectively. When the subjects were split into two groups according to age (<60 and ≥60 years), the influence of DI ≥10 on HT was strongest in the younger men (adjusted OR 4.3 (95% CI 1.0 to 19.3 v 2.1 (95% CI 0.7 to 6.5)) and the association between minimum oxygen saturation (Sao 2 ) and HT reached statistical significance in the younger men only. Conclusion: SDB is more prevalent in men with HT than in controls. DI ≥10 and lowest desaturation are independent predictors of HT irrespective of confounders. The results indicate that the influence of SDB on HT is more pronounced in younger and middle aged men than in those above 60 years.